Pain characteristics and age‐related pain trajectories in infants and young children with sickle cell disease. Issue 2 (24th September 2013) - Dampier, Carlton; Ely, Beth; Brodecki, Darcy; Coleman, Camille; Aertker, Leela; Sendecki, Jocelyn Andrel; Leiby, Benjamin; Kesler, Karen; Hyslop, Terry; Stuart, Marie
Abstract Background The epidemiology of painful episodes in infants and younger children with SCD has not been well studied, particularly for pain managed at home. Procedure SCD infants identified by newborn screening were enrolled in a longitudinal observational study of pain symptoms requiring parents to report the presence or absence of pain daily. When sickle cell related‐pain events occurred, pain occurrence, location, associated symptoms and the treatment provided also were reported. Results 103 children were enrolled at a median age of 7.2 months; 50 had an SS genotype, 32 SC, 6 SB0thalassemia, and 15 SB+thalassemia. Parents/guardians reported for a median of 3.8 years (range 0.3–7.6 years) assessing pain for a total of 141, 197 days, excluding any period of recurrent transfusions, with an additional 28, 079 days of missing data (16%). Children had pain reported on 2, 288 days (1.6%), representing 768 distinct episodes of pain, of which 108 required hospitalizations (14%). Pain locations and symptoms consistent with dactylitis were most prevalent (80%) in the 0–12 month age group, and became progressively less prevalent thereafter. Group‐based trajectory modeling of pain episode or pain day frequency identified several trajectory groups with progressively older ages of peak pain frequency, which included 40–45% of SS/SB0thalassemia and 10–12% of SC/SB+thalassemia children. Conclusions Pain is relatively infrequent in SCD infants and young children and commonly managed at home. Analyses of longitudinal pain trajectories suggest several different pain trajectories, differing in their frequency, age of onset, and age at peak pain frequency with clinical implications for hydroxyurea management. Pediatr Blood Cancer 2014;61:291–296. © 2013 Wiley Periodicals, Inc.